The failed reform to the administrators responsability regime in Colombia - Londoño Restrepo, Daniela (2018)
As a result of Law 222 from 1995, there has been presenting a modernization to the administrators liability regime, this is based on Anglo-Saxon dispositions, characterized by its flexibility and dynamism on regulating trade. Therefore, bill 070/2015 was proposed, which presented different mechanisms and concepts that were seeking to advancement the topic, mainly oriented by foreign regulations. Finally, that bill was withdrawn from Congress by of the lack of reception. However due to its necessity the bill at some point can resubmit a reform, which seeks the easing of administrators liability regime and achieve to increase the investment in domestic market.